Analysis of Banking Performance and Risk in Indonesia during the Covid-19 Pandemic - Nurseto Adhi; Sri Widiyati; Winarni; Embun Duriany Soemarso; R. Gunawan Setianegara (Indonesian Journal of Banking and Financial Technology, 2023)
The banking sector has experienced a decline in demand for credit and a lack of disbursement, which has had an impact on the income of bank credit borrowers. Knowing the financial performance of banks during the Covid-19 pandemic can provide a good explanation of the problems faced by the banking sector. The analysis used in this study was a comparative comparison of two observations using a paired sample T-test. The variables used in this study are ROA, ROE, BOPO, LDR, CAR and NPL. This research found that the Covid-19 pandemic affected the decline in bank performance in general. This can be seen in the values of ROA, ROE, RORA, NPM, LDR, and NIM which have decreased in value before and after the pandemic. This research also found that the COVID-19 pandemic increased bank risk during the pandemic. This can be seen in the BOPO and KPMM variables which have increased from before and after the pandemic.